Upiorna wersja tradycji czy romans rodzinny. Rymkiewicz i Bloom – paralela - Dembińska-Pawelec, Joanna (Śląskie Studia Polonistyczne, 2013)
The sketch presents a parallel nature of the conception of literary tradition by Jarosław Marek Rymkiewicz, and the conception of the influence by Harold Bloom. Both books: Rymkiewicz’s Czym jest klasycyzm? Manifesty poetyckie and Bloom’s The Anxiety of Influence. A Theory of Poetry appeared at the same time, namely at the end of the 1960s. The author of the sketch points to the similarities of both conceptions, showing the dependence of contemporary writers on their predecessors that are considered as “living” in the overtime duration of Tradition. She also points to the differences deriving from different inspirations by psychoanalytic conceptions, that is, Jung’s theory in the case of Rymkiewicz and Freud’s theory in the case of Bloom.